Numerical study of fluid flow and heat transfer in microchannel heat sinks using anisotropic porous media approximation - Lim F.Y.; Abdullah S.; Ahmad I. (Asian Network for Scientific Information, 2023)
In the present analysis, a microchannel heat sinks configuration was simulated by modelling the stacked microchannel heat sinks in a macroscopic scale as if it is a fluid saturated porous medium. The numerical solutions were obtained using the Brinkman and the general heat transfer based formulation. In order to accurately predict the permeability and heat transfer of the stacked microchannels, the simulations were compared with the simulation of a single microchannel heat sink assuming incompressible flow. The advantage of the proposed method is that no assumption on the laminar or fully develop nature of the flow is required. Therefore, this approach can also be used for developing flows in the channel. The important entrance effect which was neglected by previous researchers was also considered in the current simulation. Besides that, in the simulation of large microchannels stack, the proposed method reduce the computing time by approximately one order of magnitude when compared to the conventional approach of simulating individual microchannels. The extended works of the verified porous-media-like-microchannels were combined to be part of a computational domain of a CFD simulation. In the simulations, two cases were conducted under the same pump and the same pressure drops limitations. Good agreements were found with the simulations with discrepancy of 0.25-0.38%. The results were compared with numerical solutions and experimental results from the past reports. The fluid flow and thermal performance of microchannel heat sinks were well predicted with less than 5% discrepancy. 2010 Asian Network for Scientific Information.